A Review of Energy Management in Farm Automation: A Case of Paddy Plantation - Shafie, Shafini; Hami, Norsiah; Hassan, Mohamad Ghozali; Musa, Suria; Hasanah, Nur; Primaswari, Anita; Nuraisyah, Ani (Atlantis Press International BV, 2023)
Farm automation is an innovative idea that specifically manages farms via the latest technologies such as drones, robotics, and artificial intelligences with the aim to raise the quality and quantity of crops, and at the same time, optimise the labour needed by production. In other words, these technologies that are related with “smart farming” assist to make the farms more effective and automate the crops’ entire cycle. Through smart farming, main agricultural threats in the country can be diminished, the public is enticed to contribute towards the agriculture sector, the income level of local farmers will be increased, and most significantly, agricultural-based economic sectors will be transformed. Although this technology is fairly new, there is an increasing trend in the adoption of farm automation among traditional agriculture companies in Malaysia. This paper aims to review the pattern of energy management in farm automation, particularly focusing on paddy plantation. The adoption of automation and mechanisation should be further expanded to other segments of the paddy and rice supply chain. Through the review, we intend to provide better understanding related to farm energy consumption and implementation of best practices to optimise energy management on the farm, leading to better environmental performance as well great economic achievements of farmers